Fragmentos de una Artista y Formadora de Bailarines en Riohacha, La Guajira (2023)
This document compiles important parts of Yennys Diaz Berty's life as a singer, dancer, coreographer and trainer in the city of Riohacha, calling it "Fragments of an Artist and Trainer of Dancers in Riohacha, La Guajira". The life history is part of the qualitative research methods. This methodology is based on the interpretative analysis of the artistic pedagogical experience, and it is and is propitiated at the Antonio Nariño University in the bachelor's degree in Performing Arts with the Convalidation of Knowledge program.